TWO DECADES OF PERCEIVED VALUE RESEARCH IN MARKETING: A BIBLIOMETRICE ANALYSIS OF TRENDS, THEMES, AND INTELLECTUAL STRUCTURE (2000-2025) - Riyansa, Ditha (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study maps two decades (2000–2025) of customer perceived value (CPV) research in marketing to identify publication trends, intellectual structures, and emerging research fronts. Using a dual-source dataset from Dimensions.ai and Google Scholar (via Publish or Perish), this study employs three bibliometric lenses: keyword co-occurrence, source co-citation, and document bibliographic coupling. Data were processed using VOSviewer to visualize thematic clusters and evolutionary trajectories. The analysis reveals a robust intellectual backbone linking value to satisfaction and loyalty. Four dominant thematic clusters emerged: (1) the value–satisfaction–loyalty chain, (2) utilitarian versus hedonic experiential value, (3) green perceived value and ESG, and (4) digital/platform-mediated commerce. While the classic dimensional architecture (functional, social, and emotional) remains foundational, research is rapidly shifting toward live-streaming commerce, sustainability, and platform services. By triangulating two open-access databases, this review provides a more comprehensive coverage of the CPV landscape than single-source studies. It offers transparent node/edge data to support replicability and presents a prioritized research agenda for perceived value landscape evolving digital and sustainable marketing contexts Bibliometric analysis, VOSviewer, Value dimensions